2016
DOI: 10.7150/jca.15696
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Thrombospodin-2 (THBS2) Overexpression on Patients with Urothelial Carcinomas of Upper Urinary Tracts and Bladders

Abstract: Purpose: Urothelial carcinoma (UC) is a type of tumor, especially of the urinary bladder, that affects people worldwide. Clarification of its detailed tumor biology and discovery of potential targets for developing treatment strategies are imperative because of frequent recurrences and poor prognosis of advanced UCs. By data mining a published dataset of UC of bladder (UCB) transcriptome (GSE31684) from Gene Expression Omnibus, National Center of Biotechnology Information (GEO, NCBI), we identified that THBS2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 37 publications
3
27
1
Order By: Relevance
“…While Sun et al used 14 pairs of gastric tumor tissues and adjacent normal tissues in their study, we used a larger number of tissues, which makes our results more convincing. Other than gastric cancer, THBS2 has also been identified as a prognostic indicator for patients with urothelial carcinomas of the upper urinary tract and bladder [21]. Consistent with our study, in urothelial cancer, THBS2 overexpression was linked to poor prognosis, namely, disease-specific survival and metastasis-free survival.…”
Section: +supporting
confidence: 78%
“…While Sun et al used 14 pairs of gastric tumor tissues and adjacent normal tissues in their study, we used a larger number of tissues, which makes our results more convincing. Other than gastric cancer, THBS2 has also been identified as a prognostic indicator for patients with urothelial carcinomas of the upper urinary tract and bladder [21]. Consistent with our study, in urothelial cancer, THBS2 overexpression was linked to poor prognosis, namely, disease-specific survival and metastasis-free survival.…”
Section: +supporting
confidence: 78%
“…More than 90% of UCs arise in the urinary bladder, and only 5% to 10% of all UCs develop in the upper urinary tract 1-3. Although growing evidence has suggested that UBUC and upper urinary tract UC (UTUC) may share several biologically unique features, there are certain significant similarities between both types of UCs 4-9. Additionally, it was reported that there was a 30-50% risk of bladder recurrence within 5 years for patients with UTUC receiving radical nephroureterectomy and a 2-6% risk of developing subsequent UTUC after initial diagnosis with UBUC 10-11.…”
Section: Introductionmentioning
confidence: 99%
“…THBS2, secreted by stromal fibroblasts, endothelial cells and immune cells, and belongs to the THBS family of proteins, was identified in 1991 and its sequence was analyzed in 1997 (24,25). Subsequently, it was found to be associated with various cancer types (22,(26)(27)(28)(29)(30). The aim of the present study was to investigate the expression of THBS2 in CRC tissues, and determine its link with the overall survival (OS) and disease-free survival (DFS) in patients with CRC.…”
Section: Introductionmentioning
confidence: 93%